Roles of Progesterone Receptor Membrane Component 1 in Oxidative Stress–Induced Aging in Chorion Cells. (March 2019) - Feng, Liping; Allen, Terrence K.; Marinello, William P.; Murtha, Amy P.
Introduction: Oxidative stress–mediated fetal membrane cell aging is activated prematurely in preterm premature rupture of membranes (PPROMs). The mechanism of this phenomenon is largely understudied. Progesterone receptor membrane component 1 (PGRMC1) has been recognized as a potential protective component for maintaining fetal membrane integrity and healthy pregnancies. We aimed to investigate the effects of oxidative stress (represented by hydrogen peroxide [H2 O2]) on fetal membrane and chorion cell senescence, p38 mitogen-activated protein kinase (MAPK) phosphorylation, and sirtuin 3 (SIRT3) and to examine the roles of PGRMC1 in these effects. Methods: Following serum starvation for 24 hours, full-thickness fetal membrane explants and primary chorion cells were treated with H2 O2 at 100, 300, and 500 µM for 24 hours. Cells were fixed for cell senescence-associated β-galactosidase assay. Cell lysates were harvested for quantitive reverse transcription polymerase chain reaction to quantify SIRT3 messenger RNA. Cell lysates were harvested for Western blot to semi-quantify SIRT3 protein and p38 MAPK phosphorylation levels, respectively. To examine the role of PGRMC1, primary chorion cells underwent the same treatment mentioned above following PGRMC1 knockdown using validated PGRMC1-specific small-interfering RNA. Results: Hydrogen peroxide significantly induced cell senescence and p38 MAPK phosphorylation, and it significantly decreased SIRT3 expression in full-thickness fetal membrane explants and chorion cells. These effects were enhanced by PGRMC1 knockdown. Discussion: This study further demonstrated that oxidative stress–induced cell aging is one of the mechanisms of PPROM and PGRMC1 acts as a protective element for maintaining fetal membrane integrity by inhibiting oxidative stress–induced chorion cell aging.